PENGARUH PENDIDIKAN, FEE, KOMITMEN, DAN TEKANAN WAKTU PADA KINERJA AUDITOR KANTOR AKUNTAN PUBLIK - Ardika, I Gede Sunar; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2016)
Economic advancement led to the need of use of public accounting firm is growing, thus demanding a good performance of auditors to maintain public confidence. The auditor should be able to know the indicators of quality improvement performance. Knowing what the effect of educational level, the amount of the fee, organizational commitment and time pressure on the performance of the auditor is the purpose of this study. Objects in this research that the firm registered in Indonesian Institute of Certified Public Accountants (IAPI) Bali region in 2014. Data were obtained from questionnaires as many as 43 samples and analyzed using multiple linear regression techniques. The test results explained that the level of education, organizational commitment, and the positive effect of time pressure, while the amount of the fee a negative effect on the performance of auditors Public Accountant in Bali. Variable levels of education, the amount of the fee, organizational commitment, time pressure to contribute as much as 54 percent on the performance of auditors, while the remaining 46 percent is explained by other factors outside the research model.
Keywords: education level, the amount of the fee, organizational commitment, time pressures, the performance of auditors